From institutional websites to social media and mobile applications: a usability perspective - Ramos, R. (2020)
Mobile applications (MA) and social media (SM) platforms are changing Internet user behavior. This study aims to unveil within current academic literature, the fields where usability research has been focusing their efforts in the dimensions institutional websites (IW), SM and MA usability, and to suggest possible paths for future studies. Search was performed in peer-review journals, providing 302 published articles between 1994 and 2018. To examine the manuscripts, text mining (TM) was adopted to discover pertinent terms, and to reveal trends, gaps and opportunities for future research. Results show a gap on marketing and nutrition research fields and an increasing interest in the usability principles of SM technology in general. Moreover, many articles are associated with the health and medical area, suggesting a more mature development of these fields.